Pengaruh Kompetensi, Motivasi dan Perilaku Individu dengan Budaya Organisasi Sebagai Intervening Terhadap Kinerja Guru Sekolah Penuai Cibubur, Bekasi Jawa Barat - Winardi, Winardi; Prasilowati, Sri Lestari (COSMOS : Jurnal Ilmu Pendidikan, Ekonomi dan Teknologi, 2024)
Competence, motivation and individual behavior are factors that are strongly suspected of influencing teacher performance at Penuai Cibubur school. To prove the influence of the three, this study was conducted with the aim of analyzing the effect of competence, motivation and individual behavior with organizational culture as intervening on the performance of Penuai School teachers. This research was conducted at Penuai School, by taking 34 teachers as research samples, which were calculated using the Slovin formula at a 5% margin of error. Data collection used a closed questionnaire, five rating scales from strongly disagree to strongly agree, with an ordinal scale. This research was conducted quantitatively, as a data analysis tool multiple linear regression was used. While hypothesis testing is done with t-test and f-test. The study produced three main findings in accordance with the hypothesis proposed, namely, competence, motivation and individual behavior have an influence on teacher performance with organizational culture as intervening.